PENGARUH QIRA’AT AL-QUR'AN TERHADAP HUKUM FIQIH Al-HUDUD DAN AL-JIHAD - Hamdi Hamdi; Abdur Rokhim Hasan; M. Mi’raj Baharuddin; Rizky Fajar Nugraha (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
Qira’at is one of the fundamental disciplines within the sciences of the Qur’an (Ulum al-Qur’an) and plays a significant role in understanding Qur’anic meanings and deriving Islamic legal rulings. Authentic variants of Qur’anic recitation, transmitted through reliable chains back to the Prophet Muhammad (peace be upon him), provide diverse linguistic nuances that may influence legal interpretation without creating contradictions in Islamic law. This study aims to examine the influence of Qur’anic qira’at on Islamic jurisprudence, particularly in the fields of al-hudud and al-jihad. The research employs a qualitative approach using a library research method by analyzing relevant scholarly literature on qira’at and Islamic jurisprudence. The findings indicate that differences in authentic qira’at enrich the interpretation of legal verses by offering complementary meanings that support more comprehensive legal reasoning. In fiqh al-hudud, these variations strengthen the understanding of legal obligations and prohibitions, while in fiqh al-jihad, they broaden the interpretation of principles governing warfare and justice in accordance with Islamic law. In conclusion, authentic qira’at make an important contribution to the process of legal interpretation and serve as a valuable instrument in strengthening the accuracy and depth of Islamic legal derivation.